Quantitative proteomic analysis based on TMT reveals different responses of Haloxylon ammodendron and Haloxylon persicum to long-term drought - Fang Yang; Xuelian Ding; Guanghui Lv (BMC Plant Biology)
Abstract The essence of the plant drought tolerance mechanism lies in determining protein expression patterns, identifying key drought-tolerant proteins, and elucidating their association with specific functions within metabolic pathways. So far, there is limited information on the long-term drought tolerance of Haloxylon ammodendron and Haloxylon persicum grown in natural environments, as analyzed through proteomics. Therefore, this study conducted proteomic research on H. ammodendron and H. persicum grown in natural environments to identify their long-term drought-tolerant protein expression patterns. Totals of 71 and 348 differentially expressed proteins (DEPs) were identified in H. ammodendron and H. persicum, respectively. Bioinformatics analysis of DEPs reveals that H. ammodendron primarily generates a large amount of energy by overexpressing proteins related to carbohydrate metabolism pathways (pyruvate kinase, purple acid phosphatases and chitinase), and simultaneously encodes proteins capable of degrading misfolded/damaged proteins (tam3-transposase, enhancer of mRNA-decapping protein 4, and proteinase inhibitor I3), thus adapting to long-term drought environments. For H. persicum, most DEPs (enolase and UDP-xylose/xylose synthase) involved in metabolic pathways are up-regulated, indicating that it mainly adapts to long-term drought environments through mechanisms related to positive regulation of protein expression. These results offer crucial insights into how desert plants adapt to arid environments over the long term to maintain internal balance. In addition, the identified key drought-tolerant proteins can serve as candidate proteins for molecular breeding in the genus Haloxylon, aiming to develop new germplasm for desert ecosystem restoration.